2005
DOI: 10.1111/j.1365-2249.2004.02708.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclass distribution of the rheumatoid arthritis-specific autoantibodies to citrullinated fibrin

Abstract: SummaryIn the rheumatoid synovium, deiminated ('citrullinated') forms of fibrin are the major targets of IgG autoantibodies to citrullinated proteins (ACPA), the most specific serological markers of rheumatoid arthritis (RA). To further the characterization of ACPA, we determined their subclass distribution. From a previously validated highly sensitive and specific enzyme-linked immunosorbent assay (ELISA) onto in vitro deiminated human fibrinogen ----antihuman fibrin(ogen) autoantibodies (AhFibA)-ELISA ----we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 54 publications
7
73
1
Order By: Relevance
“…In addition, an analysis of synovial tissue from a patient with rheumatoid arthritis has demonstrated that 51 (5.2%) of 990 identified synovial proteins exhibited citrullination, and 13 citrullinated autoantigens could unambiguously be assigned by mass spectrometry (54). Apart from fibrinogen, a major citrullinated autoantigen in these patients (55,56), all other proteins identified in this study (54) were polypeptides for which citrullination had not been described previously. Similarly, a comparative proteomic study (see Ref.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, an analysis of synovial tissue from a patient with rheumatoid arthritis has demonstrated that 51 (5.2%) of 990 identified synovial proteins exhibited citrullination, and 13 citrullinated autoantigens could unambiguously be assigned by mass spectrometry (54). Apart from fibrinogen, a major citrullinated autoantigen in these patients (55,56), all other proteins identified in this study (54) were polypeptides for which citrullination had not been described previously. Similarly, a comparative proteomic study (see Ref.…”
Section: Discussionsupporting
confidence: 55%
“…ACPA are polyclonal in the usage of different IgG subclasses, but in this case the pattern is more heterogeneous. So far the studies conducted indicate the dominance of IgG1 and IgG4, while IgG3 have been detected with cyclic citrullinated peptide (CCP) and vimentin, but not with fibrinogen 4,5 .…”
Section: To the Editormentioning
confidence: 99%
“…Apart from giving rise to, possibly false, high RF titers, this Fcmediated binding of IgG4 to IgG1 Abs may result in overestimated values for IgG4 in binding assays involving catching Abs, depending on the animal source. Elevated levels of IgG4 are associated with other RA-related autoantibodies as well (7).…”
mentioning
confidence: 99%